Integrating metallic cobalt and N/B heteroatoms into porous carbon nanosheets as efficient sulfur immobilizer for lithium-sulfur batteries. (15th October 2020) - Zhang, Ze; Xiong, Dong-Gen; Shao, A-Hu; Huang, Xiao-Yun; Huang, Yan; Yu, Ji; Cai, Jian- Xin; Yang, Zhen-Yu
Abstract: A major challenge for the practical application of lithium-sulfur batteries is the polysulfide shuttling and sluggish redox kinetics due to the notorious adsorption-catalysis underperformance. However, conventional carbonaceous materials generally suffer from poor adsorption of polysulfides due to their intrinsic nonpolar surface. Herein, porous carbon nanosheets modified with metallic cobalt and nonmetallic nitrogen/boron heteroatoms, denoted as Co-NBC, is reported as sulfur immobilizer. The presence of conductive metallic cobalt as well as the doped N/B heteroatoms can enhance the electronic conductivity of carbon matrix, and significantly improve the chemical entrapment of soluble polysulfides. Kinetics measurements show that metallic Co catalysts can greatly promote the polysulfide redox kinetics of both liquid-liquid and liquid-solid conversion. As a result, the S/Co-NBC composite realizes remarkable rate performance with high specific capacity of 509 mAh g −1 at a high C-rate of 5 C, and excellent cycle stability with a low capacity fading rate of ∼0.09% per cycle within 500 cycles. Moreover, the S/Co-NBC cathodes realize promising cycle performance even at harsh working condition of high sulfur loading (∼4.6 mg cm −2 ) or low electrolyte addition (∼3 μL mg −1 ). This work proposes a meaningful strategy to obtain efficient carbon nanomaterials for high-performance Li–S batteries. Graphical abstract: Image 1